On Theory, Models, Model-Testing, and Estimation - Greenberg, David F. (Journal of quantitative criminology, 2001)
I reply to comments and criticisms of my article raised in this Special Issue by Cantor and Land, Britt, O'Brien, Levitt, and Paternoster and Bushway.